Antibiofilm formation activity of lupinifolin isolated from Derris reticulata stems against Enterococcus faecalis - Pawitra Pulbutr; Kridsanun Seelakot; Nicharee Kumphupong; Sakulrat Rattanakiat (Shahrekord University of Medical Sciences, 2024)
Introduction: The biofilm formation capability of Enterococcus faecalis is one of the key virulence factors contributing to its multidrug resistance and therapeutic challenges. Lupinifolin, a prenylated flavanone extracted from the stems of Derris reticulata Craib., possesses antibacterial properties against a range of gram-positive cocci. This study aimed to investigate the effects of lupinifolin alone or in combination with vancomycin against E. faecalis biofilm formation at different incubation durations, presumably representing different biofilm stages. Methods: The crystal violet biofilm formation assay and the micro-broth dilution method were used to measure the antibiofilm and antibacterial activities, respectively. Results: Lupinifolin did not inhibit E. faecalis growth at the highest concentration tested, i.e., minimum inhibitory concentration (MIC) > 128 µg/mL. However, lupinifolin at the sub-MICs (16-128 µg/mL) possessed a significant inhibition against E. faecalis biofilm formation at every incubation time of 6, 12, 24, and 36 hours. Lupinifolin had the lowest median inhibitory concentrations (IC50) of 6.78 ± 3.04 µg/mL after incubation for 6 hours. Thus, the antibiofilm action of lupinifolin was most likely produced predominantly at the first stage of biofilm formation, known as initial surface attachment. The sub-MICs of lupinifolin also significantly enhanced the antibiofilm activity of vancomycin at relatively low concentrations of ¼ MIC (2 µg/mL) and 1 / 8 MIC (1 µg/mL), specifically at 6- and 36-hour incubation (P<0.05). Conclusion: These results point to lupinifolin's potential use against E. faecalis as an antibiofilm agent. Nonetheless, more research is needed to identify the exact antibiofilm mechanism of lupinifolin.